2011
DOI: 10.1162/jocn.2010.21585
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Musical Expertise on Segmental and Tonal Processing in Mandarin Chinese

Abstract: A same-different task was used to test the hypothesis that musical expertise improves the discrimination of tonal and segmental (consonant, vowel) variations in a tone language, Mandarin Chinese. Two four-word sequences (prime and target) were presented to French musicians and nonmusicians unfamiliar with Mandarin, and event-related brain potentials were recorded. Musicians detected both tonal and segmental variations more accurately than nonmusicians. Moreover, tonal variations were associated with higher err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
152
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(166 citation statements)
references
References 67 publications
10
152
0
Order By: Relevance
“…Much evidence for such unification has been found in previous studies (e.g. Delogu et al, 2006;Marie et al, 2011;Tillmann et al, 2011;Wong & Perrachione, 2007). For tone language listeners, however, pitch perception taps into different mechanisms, being used in linguistic contexts to differentiate phonological categories, and in musical contexts as perception of fine acoustical differences.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Much evidence for such unification has been found in previous studies (e.g. Delogu et al, 2006;Marie et al, 2011;Tillmann et al, 2011;Wong & Perrachione, 2007). For tone language listeners, however, pitch perception taps into different mechanisms, being used in linguistic contexts to differentiate phonological categories, and in musical contexts as perception of fine acoustical differences.…”
Section: Introductionmentioning
confidence: 88%
“…languages in which pitch variations are used to distinguish meaning lexically) are beneficial to pitch processing in the complementary domain. With regard to the enhancement in lexical tone perception brought about by music aptitude, it has been found that, compared to non-tone language speakers without music training, non-tone language musicians are better at detecting lexical tonal variations (Alexander, Wong, & Bradlow, 2005;Delogu, Lampis, & Belardinelli, 2006;Marie, Delogu, Lampis, Belardinelli, & Besson, 2011), and learning to pair pitch patterns to word meaning (which is similar to learning lexical tones) (Wong & Perrachione, 2007). Speaking a tone language has also been found to be beneficial for music perception (Alexander, Bradlow, Ashley, & Wong, 2008;Bidelman, Hutka, & Moreno, 2013;Jiang, Hamm, Lim, Kirk, & Yang, 2010;Pfordresher & Brown, 2009;Stevens, Keller, & Tyler, 2004;Tillmann et al, 2011;Wong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In marked contrast, for Tagalog, WM and the rhythmic discrimination ability for musical statements contributes to explaining the variability of the imitations of the participants, illustrating that there are individual differences in the positive transfer from music to languages. Thus pitch discrimination ability is more important for tone languages than for non-tone languages, especially as in those languages where pitch fine-tuning is necessary to determine meaning (Marie, Delogu, Lampis, Belardinelli, & Besson, 2011). This suggests that those who learn tone languages as a second language may benefit from musical aptitude and musical training as this impacts pitch perception abilities of tone languages in general (Besson, Schön, Moreno, Santos, & Magne, 2007).…”
Section: Music Perception: Tone Languages Versus Non-tone Languagesmentioning
confidence: 99%
“…On top of enhanced processing pertaining to pitch, musicians are found to be more sensitive to timbre than non-musicians (Chartrand and Belin, 2006), an acoustic property assumed to contribute to voice quality and emotion in speech (Juslin and Laukka, 2003). Meanwhile, musicians are also reported to outperform non-musicians in other language tasks such as second language production and perception, pitch memory, verbal memory, and perhaps segmental processing (Bidelman et al, 2013;Chan et al, 1998;Slevc and Miyake, 2006;Marie et al, 2011; although see Delogu et al, 2010). In the current study, the talker identification task in each language condition involved five different talkers and was cognitively more complex than pitch perception.…”
Section: A the Impact Of Musical Training On Pitch And Talker Identimentioning
confidence: 99%